Social‐benefits stigma and subsequent competitiveness. - Valdez Gonzalez, Natalia I.; Brown, Alexander L.; Palma, Marco A. (Economic Inquiry, 2025)
We conduct a laboratory experiment to explore how benefit‐eligibility stigma drives subsequent decisions to enter competition. We induce a stigma associated with a low‐status benefit and then introduce "plausible deniability" to reduce this stigma by expanding benefit eligibility to a middle‐status group. When newly‐eligible individuals qualify for the benefit, their rate of entry into a subsequent and unrelated tournament is reduced by 17–20 percentage points compared to the treatment in which they do not qualify. A potential interpretation of our results would suggest expanding for certain government assistance programs may produce unintended consequences for the newly eligible.